Marine heatwaves alter shell microbiomes and denitrification capacity: An oyster family-specific response - Giulia Filippini; Ana B. Bugnot; Wayne O'Connor; Paul E. Gribben; Deepa R. Varkey; Ian T. Paulsen; Katherine A. Dafforn (Marine Pollution Bulletin, 2026)

Above and below-ground bacterial communities shift in seagrass beds with warmer temperatures - Luke DA. Walker; Paul E. Gribben; Tim M. Glasby; Ezequiel M. Marzinelli; Deepa R. Varkey; Katherine A. Dafforn (Frontiers in Marine Science, 2024)
Current rates of ocean warming are predicted to exacerbate ongoing declines in seagrass populations. Above-ground responses of seagrass to increasing temperatures have been studied from a direct physiological perspective while indirect effects, including changes to microbially-mediated below-ground processes, remain poorly understood. To test potential effects of increased temperature on seagrass growth and associated microbial communities, we sampled seagrass beds experiencing ambient and elevated water temperatures at Lake Macquarie, Australia. Sites with warmer water were associated with a plume from a power station discharge channel with temperatures analogous to conditions predicted by 2100 under current rates of ocean warming (+3°C). The microbial community composition in both sediments and leaf tissues varied significantly between warm and ambient water temperatures with higher relative abundances of putative sulphate-reducing bacteria such as Desulfocapsaceae, Desulfobulbaceae and Desulfosarcinaceae in sedimentary communities in warm water. Above-ground biomass and seagrass growth rates were greater at warm sites while below-ground biomass and detrital decomposition rates showed no difference suggesting potential buffering of temperature effects below-ground. These findings suggest a 3°C rise in temperate regions is unlikely to induce mortality in seagrass however, it may shift microbial communities towards more homogenous structure and composition.

Nitrogen-cycling genes in oyster reefs and surrounding sediments: Relationships with environmental factors and respective nitrogen rates - Giulia Filippini; Ana B. Bugnot; Deepa R. Varkey; Nachshon Siboni; Angus Ferguson; Paul E. Gribben; Katherine Erickson; Julia Palmer; Katherine A. Dafforn (Marine Pollution Bulletin, 2023)

Single-Turnover Variable Chlorophyll Fluorescence as a Tool for Assessing Phytoplankton Photosynthesis and Primary Productivity: Opportunities, Caveats and Recommendations - Nina Schuback; Philippe D. Tortell; Ilana Berman-Frank; Douglas A. Campbell; Aurea Ciotti; Emilie Courtecuisse; Zachary K. Erickson; Tetsuichi Fujiki; Kimberly Halsey; Anna E. Hickman; Yannick Huot; Maxime Y. Gorbunov; et al. (Frontiers in Marine Science, 2021)
Phytoplankton photosynthetic physiology can be investigated through single-turnover variable chlorophyll fluorescence (ST-ChlF) approaches, which carry unique potential to autonomously collect data at high spatial and temporal resolution. Over the past decades, significant progress has been made in the development and application of ST-ChlF methods in aquatic ecosystems, and in the interpretation of the resulting observations. At the same time, however, an increasing number of sensor types, sampling protocols, and data processing algorithms have created confusion and uncertainty among potential users, with a growing divergence of practice among different research groups. In this review, we assist the existing and upcoming user community by providing an overview of current approaches and consensus recommendations for the use of ST-ChlF measurements to examine in-situ phytoplankton productivity and photo-physiology. We argue that a consistency of practice and adherence to basic operational and quality control standards is critical to ensuring data inter-comparability. Large datasets of inter-comparable and globally coherent ST-ChlF observations hold the potential to reveal large-scale patterns and trends in phytoplankton photo-physiology, photosynthetic rates and bottom-up controls on primary productivity. As such, they hold great potential to provide invaluable physiological observations on the scales relevant for the development and validation of ecosystem models and remote sensing algorithms.

Revealing changes in the microbiome of Symbiodiniaceae under thermal stress - Emma F. Camp; Tim Kahlke; Matthew R. Nitschke; Deepa Varkey; Nerissa L. Fisher; Lisa Fujise; Samantha Goyen; David J. Hughes; Caitlin A. Lawson; Mickael Ros; Stephen Woodcock; Kun Xiao; et al. (Environmental Microbiology, 2020)
Summary Symbiodiniaceae are a diverse family of marine dinoflagellates, well known as coral endosymbionts. Isolation and in vitro culture of Symbiodiniaceae strains for physiological studies is a widely adopted tool, especially in the context of understanding how environmental stress perturbs Symbiodiniaceae cell functioning. While the bacterial microbiomes of corals often correlate with coral health, the bacterial communities co‐cultured with Symbiodiniaceae isolates have been largely overlooked, despite the potential of bacteria to significantly influence the emergent physiological properties of Symbiodiniaceae cultures. We examined the physiological response to heat stress by Symbiodiniaceae isolates (spanning three genera) with well‐described thermal tolerances, and combined these observations with matched changes in bacterial composition and abundance through 16S rRNA metabarcoding. Under thermal stress, there were Symbiodiniaceae strain‐specific changes in maximum quantum yield of photosystem II (proxy for health) and growth rates that were accompanied by changes in the relative abundance of multiple Symbiodiniaceae‐specific bacteria. However, there were no Symbiodiniaceae‐independent signatures of bacterial community reorganisation under heat stress. Notably, the thermally tolerant Durusdinium trenchii (ITS2 major profile D1a) had the most stable bacterial community under heat stress. Ultimately, this study highlights the complexity of Symbiodiniaceae‐bacteria interactions and provides a first step towards uncoupling their relative contributions towards Symbiodiniaceae physiological functioning.